Analisis Konservasi Air Berbasis Zero Run Off (Studi Kasus Kawasan Block Office Balai Kota Among Tani Kota Batu) - Dini Rosvita Tri A.; Mohammad Bisri; Ussy Andawayanti (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
The development of Batu as a tourist and agropolitant city has led to some concern, such as water resources. The number of springs has increasingly declined due to the conversion of forest into agriculture land, residential, and tourist sites. Therefore, it is necessary to maintain equilibrium through the process of extracting and replenishment of rain water by absorbing it into soil pores as water conservation efforts. This study examines the analysis of water conservation based on the concept of zero runoff, located in the Block Office area. It is expected to become input for the Batu City Government and be developed in those area. The analysis of surface runoff is calculated by Rational Method. The dimension of recharged well is calculated by using SNI method 03 2453 2002. The magnitude of design discharge obtained with 5 years return period is 111,408 mm. Reharged well is planned with 5 meters height and 1 meter diameter. Recharged well used for 100 m roof area is 1. Water conservation technology by using recharged well is able to collect runoff from the roof, while retention pool collect and absorb runoff from the parking area, road, and yard.